Biological Acoustic Levitation and Its Potential Application for Microgravity Study - Taylor Boudreaux; Luke Freyhof; Brandon D. Riehl; Eunju Kim; Ryan M. Pedrigi; Jung Yul Lim (Bioengineering)
The open and contactless environment of acoustic levitation provides a unique condition in experimenting with varying substances while levitated for observation and implementation with other devices, with recent improvements in cost and accessibility. We briefly decipher the theory behind acoustic levitation and describe currently available levitation platforms. Then, how these platforms have been employed in biological applications is reviewed. Intriguingly, recent researches indicated the viability of acoustic levitation to be utilized as a microgravity simulator. We introduce existing on-ground microgravity platforms, and discuss the potential of acoustic levitation in simulating microgravity. Acoustic levitation could be an alternative to microgravity platforms such as clinostats while allowing for novel microgravity research. On the other hand, the microgravity provided by acoustic levitation may be restricted due to potential limitations in the available levitation volume, relatively larger gravity compared to 10−3 g centrifugal acceleration from clinostats, and probable instability due to air perturbations and acoustic streaming. With more knowledge about in-droplet particle rotation and the regulatory factors during levitation, acoustic levitation may provide a new and advanced platform for microgravity simulation via taking advantage of its availability for real-time observation and manipulation of samples via added instrumentation while samples are levitated in a simulated microgravity condition.